The Percentage of Epiphytes Cover on The Seagrass Beds in Sepanjang Beach, Indonesia - Listiawati, Vina; Rohmah, Siti Naily; Alfan, Dheny Choirul (Bioeksperimen: Jurnal Penelitian Biologi, 2018)
Seagrasses are foundation plant species as they not only create their own habitat but also for other marine organisms. In estuarine and marine environments, they form beds and their leafy structure are the excellent substrate for the epiphytes. In this study, we aimed to investigate the percentage cover of epiphytes on the seagrass beds in Sepanjang Beach, Indonesia. 5 transect lines with 20 m in length with the 50 x 50 cm quadrat at the interval of 5 m were placed at the perpendicular angle to the shoreline. These transects were positioned from the furthermost of the western part to the middle part of the beach, represented the gradation level of human activities. The result showed that the percentage cover of epiphytes was significantly higher on the middle part of the beach compared to the side of the beach. This present study suggest that human activities could lead to the increasing of epiphytes cover on the seagrass beds.